Prophetic based transformational leadership in educational institutions - Puspasari, Maria Dwi; Fahrudin, Adi; Bariyah, N. Oneng Nurul (Technium Social Sciences Journal, 2022)
The results of the research that the author did, strengthen the theory of transformational leadership James Mac Gregor Burn. However, in this study, the author uses an approach with prophetic values. This study aims to analyze prophetic-based transformational leadership. The focus of the research is: (1). How is the prophetic-based transformational leadership strategy (2) What are the obstacles faced in solving problems (3). How to evaluate prophetic-based transformational performance. This research is qualitative research through a descriptive approach. The data was obtained by taking primary data by conducting interviews. And secondary data through literature reviews, supporting documents, archives, and observations needed by the author related to this research. Data were analyzed through data reduction, followed by data presentation and then drawing conclusions. The research was conducted at STAI Madinatul Ilmi, Depok, West Java, Indonesia. The results of the research found that; a prophetic-based transformational leadership strategy at STAI Madinatul Ilmi formulated the vision and mission to achieve the goals that have been set. determined through a SWOT analysis at STAI Madinatul Ilmi. Then nine main strategies were established, namely, the field of student affairs, improving the quality of lecturers, curriculum, facilities and infrastructure, funding, program management, learning processes, graduates as well as research and publications. Another result of this study found that the role of transformational leadership in dealing with existing problems is carried out by outlining the eight main strategies that have been set. While the implementation is carried out on a prophetic basis. Finally, results also found that evaluations that can be carried out formally or informally are carried out continuously in all fields and in all ranks at STAI Madinatul Ilmi in order to find out how far the programs have been determined have been carried out properly or not.